Programa educativo motivación en inteligencia emocional en estudiantes de la escuela superior de formación artística pública bellas artes Iquitos 2024 - Pinedo Meza, Enrique (2025)
The study determined: To verify to what extent the Motivation Educational Program improves Emotional Intelligence in students of the E.S.F.A.P. Bellas Artes of the city of Iquitos during the year 2024. Using a quantitative pre experimental approach, a study was conducted with a group of 48 young people, who served as population and census sample, enrolled in the E.S.F.A.P. Bellas Artes (2020 - 2024). An evaluation was applied to these students before and after an educational program called “Motivation”, through an observation sheet in 12 learning sessions, carried out throughout the academic semester 2024 II. Subsequently, a descriptive analysis was performed on emotional intelligence, evaluating its dimensions and indicators before and after the program. The inferential analysis was carried out using the nonparametric statistical test of ranks with Wilcoxon sign, establishing a significance level of α = 0.05 (5%). The test statistic used was the standardized Z-score. With an error level of 0.001% and a confidence level of 95%, the research hypothesis was approved: the Educational Program "Motivation" improves emotional intelligence in Fine Arts students in the city of Iquitos during the year 2024.